1997
DOI: 10.1159/000237544
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Corticosteroid Resistance in Asthmatic Patients

Abstract: Corticosteroid-resistant (CR) asthma is associated with disease chronicity, a more frequent family history of asthma and impaired in vitro and in vivo responsiveness of peripheral blood mononuclear cells to the suppressive effects of glucocorticoids. CR asthma is associated with normal suppression of the hypothalamic-pituitary-adrenal axis and of biochemical indices of bone turnover by dexamethasone, indicating that the phenomenon of glucocorticoid resistance is specific to inflammatory leukocytes and that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 21 publications
(25 reference statements)
0
13
0
1
Order By: Relevance
“…53 This breed of rat also exhibits airway hyper-responsiveness after exposure to allergens. 54 In human studies, a subset of asthma patients 55,56 as well as a subset of persons with depression exhibit evidence of glucocorticoid resistance. 57,58 Additional controlled studies are needed, examining the prevalence of depression in asthma patients and persons with comparable disability from other general medical conditions, to determine if asthma patients are at increased risk of depression compared with other general medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…53 This breed of rat also exhibits airway hyper-responsiveness after exposure to allergens. 54 In human studies, a subset of asthma patients 55,56 as well as a subset of persons with depression exhibit evidence of glucocorticoid resistance. 57,58 Additional controlled studies are needed, examining the prevalence of depression in asthma patients and persons with comparable disability from other general medical conditions, to determine if asthma patients are at increased risk of depression compared with other general medical conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical Study G Vannucchi and others Steroid therapy in Graves' orbitopathy 170:1frequently observed; this situation has been reported in as many as 50% of patients who present with severe and difficult-to-treat asthma (17,18). In this study, we have not been able to find GR variants that were significantly associated with either the therapeutic response or the occurrence of adverse events.…”
Section: European Journal Of Endocrinologymentioning
confidence: 98%
“…This suggests that these patients are relatively resistant to the anti-inflammatory effects of GCS and may be part of a continuum, as described above. The mechanisms of relative GCS resistance are not yet known, as these patients are difficult to investigate with invasive techniques (62). Studies with biopsies, bronchoalveolar lavage and induced sputum have shown that inflammation persists, despite high doses of GCS and there is an increase in neutrophils in the airways of these patients (63,64).…”
Section: Glucocorticosteroid Resistant and Dependent Asthmamentioning
confidence: 99%